Neoplasia in the dromedary camel: a review (Camelus dromedarius) - Abu Damir, Hassan; Tageldin, Mohamed H.; Ali, Mahmoud A.; Adem, Abdu (Frontiers in Veterinary Science, 2025)
BackgroundDromedary camels are a source of milk, meat, wool, and income in poor societies and play an important role in social events. Tumors have devastating effects on the health, production, reproduction, and marketing value of dromedaries. Reviews on neoplasia in dromedaries are scarce, making it pertinent to present this comprehensive study.AimThis review provides insights into the epidemiology, pathology, future diagnosis, and treatment of camel tumors.MethodsThe literature on tumors in dromedaries is reviewed with a focus on tumor types in different body systems, epidemiology, risk factors, future diagnosis, and treatment. Epidemiological data were collected from various sources, analyzed, and presented according to body systems. The relative frequencies of malignant and benign tumors were displayed.ResultsThe relative frequencies of tumors in camels were as follows: skin (54.8%), reproductive (23.0%), lymphoid (6.9%), and gastrointestinal (6.3%). The common malignant and benign tumors were observed in the following order: carcinomas (35.5%), fibromas (11.2%), teratomas (7.8%), lymphomas and leukemia (7.4%), papillomas (6.2%), and adenomas (6.2%). A recent rise in tumor cases was observed. Possible risk factors included contamination of feed with fungal toxins and exposure to pesticides, herbicides, hydrocarbons, and heavy metals from the petroleum industry and gold mining. Other risk factors included environmental changes or famine, certain veterinary drugs and hormones, plant carcinogens, ultraviolet light, familial predisposition, and old age. The contraction of bovine papillomavirus (PV) during movement to new areas with denser animal populations is also likely.ConclusionDifferent tumor types were reported in various body systems of the dromedary, with carcinomas, fibromas, teratomas, lymphomas/leukemia, and papillomas being the most common. An increase in tumor reports in camels is expected due to recent advancements in camel farming systems, specialized breeding centers, improvements in veterinary services, and enhanced disease surveillance. Some skin tumors, such as papillomas/fibropapillomas, exhibited koilocytosis, possibly caused by different PV strains, which may warrant further investigation. Abattoir tumor surveys may show bias, as dromedaries presented for slaughter were typically barren females or young males. Various diagnostic methods were discussed, and future advanced technologies for tumor diagnosis and treatment in camels, including targeted therapy and precision medicine, were suggested.